PENGARUH PERPUTARAN KAS, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Aninda Christianti, 15.05.61.0014; Sudarsi, sri (Students' Journal of Economic and Management, 2019)
This study is a research that examines and analyse the effect of cash turn over, Capital Structure and firm size towards profitability (Return on Assets) of companies listed on Indonesia Stock Exchange 2015-2017. This study used purposive sampling method with sample size as 225 manufacture companies. Hypothesis testing using t-test with 5% significance level. The result showed that cash turn over has negative significant effect toward Return on Assets, Capital structure has negative significant toward Return on Assets, while firm size has positive and significant effect toward Return on Assets.